2021
DOI: 10.3390/jmse9050519
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Atlantic Meridional Circulation during Deglacial Climates Inferred from Planktonic Foraminiferal Shell Weights

Abstract: Changes in the density structure of the upper oceanic water masses are an important forcing of changes in the Atlantic Meridional Overturning Circulation (AMOC), which is believed to widely affect Earth’s climate. However, very little is known about past changes in the density structure of the Atlantic Ocean, despite being extensively studied. The physical controls on planktonic foraminifera calcification are explored here, to obtain a first-order approximation of the horizontal density gradient in the eastern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…Since late Pliocene atmospheric pCO 2 concentrations are comparable to today (Seki et al, 2010;Martıńez-Botı́et al, 2015) and global temperatures 2 to 3°C warmer (Haywood et al, 2016), higher pelagic calcification may be the result of the influence of the intense, warm and saltier (~1 kg/m 3 denser) Mediterranean outflow to the Atlantic during the late Pliocene that altered the N. Atlantic oceanography (Kheĺifi et al, 2009). Along the transect, the solid test fraction of G. ruber albus varies by 55%, while for other globigerinids in the Atlantic the test fraction was found to vary up to 110% across the last glacial maximum (Zarkogiannis, 2021). This enhanced plasticity of the extent of sea surface plankton shell precipitation may be an important factor in regulating atmospheric CO 2 over the geologic time, since the production of biogenic CaCO 3 affects the alkalinity of seawater and thus the capacity of the ocean to absorb CO 2 from the atmosphere (Zondervan et al, 2001).…”
Section: Foraminifera Shell Bulk Densitiesmentioning
confidence: 91%
“…Since late Pliocene atmospheric pCO 2 concentrations are comparable to today (Seki et al, 2010;Martıńez-Botı́et al, 2015) and global temperatures 2 to 3°C warmer (Haywood et al, 2016), higher pelagic calcification may be the result of the influence of the intense, warm and saltier (~1 kg/m 3 denser) Mediterranean outflow to the Atlantic during the late Pliocene that altered the N. Atlantic oceanography (Kheĺifi et al, 2009). Along the transect, the solid test fraction of G. ruber albus varies by 55%, while for other globigerinids in the Atlantic the test fraction was found to vary up to 110% across the last glacial maximum (Zarkogiannis, 2021). This enhanced plasticity of the extent of sea surface plankton shell precipitation may be an important factor in regulating atmospheric CO 2 over the geologic time, since the production of biogenic CaCO 3 affects the alkalinity of seawater and thus the capacity of the ocean to absorb CO 2 from the atmosphere (Zondervan et al, 2001).…”
Section: Foraminifera Shell Bulk Densitiesmentioning
confidence: 91%
“…1 and 2), the equivalent ice-shelf thinning rate, ℎ ̇𝑒𝑞 , required to induce such a migration can thus be approximated from hydrostatic principles 27,69,70 represents the buoyancy term of floating ice in ocean water according to the depthaveraged density of sea water (𝑝 𝑤 ; 1027.5 kg m -3 ) and meteoric ice (𝑝 𝑖 ; 917 kg m -3 ), respectively; 𝑧̇ is the change in ocean tide over the period of grounding-line retreat; 𝛼 and 𝛽 are the surface and basal slopes of the ice, respectively; and 𝑥̇ is the rate of grounding-line migration (positive for retreat). We ascribed a seawater density of 1027.5 kg m -3 following research that has suggested that density values in the eastern North Atlantic were not significantly different during the last deglaciation compared to present-day 71 , and assumed the surface slope of the ice sheet, α, to be flat at the time of corrugation ridge formation (Fig. 4).…”
Section: Equivalent Ice-shelf Thinningmentioning
confidence: 99%
“…The book Climate Change and Marine Geological Dynamics includes nine contributions [1][2][3][4][5][6][7][8][9] to this Special Issue published during 2020-2021. Overall, the aim of this Special Issue is to collect studies that provide new views on marginal and open marine geological phenomena and processes by using different methodologies and approaches.…”
mentioning
confidence: 99%
“…Zarkogiannis (2021) [7], using species-specific planktonic foraminifera shell weights succeeds in obtaining a first-order approximation of the horizontal density gradient of the eastern Atlantic during the last 200,000 years and reports two instances of disruption of the Atlantic Ocean Meridional Circulation. Published records of Globigerina bulloides shells from the North and Tropical eastern Atlantic were complemented by the analysis of a South Atlantic core.…”
mentioning
confidence: 99%